The Relationship between Satisfaction, Interaction, E-learning Readiness, and Academic Achievement in Online Learning - Ayşe Bağrıacık Yılmaz (Open Praxis, 2023)
In this study, the relationship between students’ e-learning readiness, perceptions of interaction in online learning environments, satisfaction, and academic achievement was examined. The research was conducted according to correlational study principles. The academic achievement variable of the study was determined based on the final exam grades of the students, and three separate scales were used for other variables. The data of the study were obtained from 212 students who received fully online education. The data obtained were analyzed by structural equation modelling method. According to the results of the study, e-learning readiness and interaction perception are predictors of satisfaction in online learning environments. The effect of interaction on satisfaction was found to be higher. There is a moderate relationship between student-content and student-instructor interaction dimensions of interaction and satisfaction. There is a low level relationship between many dimensions of e-learning readiness and satisfaction. However, e-learning readiness, interaction, and satisfaction are not predictors of academic achievement. Moreover, no significant relationship was found between e-learning readiness and interaction. Based on the findings of the study, various comments and suggestions were made regarding better online learning environments.